Impact of COVID-19 Pandemic on the Trends of Trichomonas vaginalis Infection in a Tertiary Hospital of Madrid, Spain - Celia Bolumburu; Vega Zamora; María Muñoz-Algarra; Maria Luisa de la Cruz Conty; José Antonio Escario; Alexandra Ibáñez-Escribano (Microorganisms, 2024)
More than one million sexually transmitted infections (STIs) occur every day, and Trichomonas vaginalis is responsible for more than 156 million cases each year worldwide. Nevertheless, epidemiological studies of this parasite in Europe are scarce. The aim of this study was to evaluate the impact that the COVID-19 pandemic may have had in the diagnosis and epidemiology of trichomoniasis. All available data from January 2018 to December 2021 for T. vaginalis isolation on gynecologic patients attending a Spanish Tertiary Hospital were analyzed. Pre-pandemic results (2018–2019) were compared to pandemic results (2020–2021). The pre-pandemic T. vaginalis prevalence in women was 1.15% (95% Confidence Interval, CI: 0.94–1.41), and significantly decreased in 2020–2021 (0.77%, 95% CI: 0.57–1.03; p = 0.025). Demographic nor clinical characteristics of women diagnosed with trichomoniasis did not statistically differ between the periods, although an increase in chlamydia co-infected patients was observed in the latest (from 8% in 2018–2019 to 19% in 2020–2021). This study has detected a decrease in the diagnosis of trichomoniasis; however, this is probably due to the increase in the healthcare pressure triggered by the pandemic. More than 75% of the cases diagnosed in 2021 occurred in the second half, which suggests that special attention should be given to the evolution in the coming years once normality has been restored in hospitals. Moreover, these results warn of the lack of routine diagnosis of trichomoniasis during pregnancy and the absence of specific protocols for possible co-infections, which could become a strategy to reduce the growing trend of STIs, including T. vaginalis detection, as an interesting marker of sexual risk behaviors.